Heel fat pad syndrome beyond acute plantar fascitis. (September 2021) - Balius, Ramon; Bossy, Mireia; Pedret, Carles; Porcar, Carme; Valle, Xavier; Corominas, Hèctor
Graphical abstract: Fibrosis and atrophy. MRI study in T1 sequence (a) and T2-STIR sequence (b) characterized by changes in signal intensity with low-signal intensity bands (*). Short-axis (c) and long-axis (d) of grey scale ultrasound where a thickness reduction of heel fat tissue is observed with overall normal echogenicity. Highlights: Heel pain is a frequent cause of pain and disability in adult active population. Pathological findings of the heel fat pad area using MRI and US can provide a differential diagnosis of heel pain beyond plantar fasciitis. Observational case series study of patients with fat pad atrophy in the plantar aspect of the heel with a bed-side exam with US. Abstract: Heel pain is a frequent cause of pain and disability in adult active population. In patients with this clinical presentation, several causes must be ruled out, among them plantar fasciitis the most common. Other etiologies of plantar heel pain are the entrapment of muscular branch of the lateral plantar nerve (Baxter nerve) or fat pad atrophy, being the last one the second cause of heel pain after plantar fasciitis. A case series of patients with pathological findings of the heel fat pad area using MRI and US to provide a differential diagnosis of heel pain. Observational case series study. Nine patients visited presented with pain in the plantar aspect of the heel. The plantar aspect of the heel was evaluated in detail with US and MRI. Main inclusion criteria were to present acute or chronic pain on the plantar aspect. In five cases the right heel was affected, in three cases the left heel. One case presented bilateral complaints. All patients presented mechanical pain. Specifically, four of them also described a constant clunk during footstep. Heel fat pad lesion was confirmed with MRI and US in the medial aspect, observed in five patients. In four patients, the heel fat pad was globally affected respectively. This case series tries to put some light on other heel conflicts beside plantar fasciitis that should be ruled out, being one of those, heel fat pad atrophy. Our presentation highlight the role that bed side ultrasound can play in the definition of a specific pattern confirmed with MRI after the US.